Passivation of interfaces in thin film solar cells: understanding the effects of a nanostructured rear point contact layer - Salomé, Pedro M. P. (2021)
Thin film solar cells based in Cu(In,Ga)Se2 (CIGS) are among the most efficient polycrystalline solar cells, surpassing CdTe and even polycrystalline silicon solar cells. For further developments, the CIGS technology has to start incorporating different solar cell architectures and strategies that allow for very low interface recombination. In this work, we study and characterize ultrathin 350 nm CIGS solar cells with a rear interface passivation strategy. The rear passivation was achieved using an Al2O3 nanopatterned point structure. Using the cell results, photoluminescence measurements and detailed optical simulations based on the experimental results, we show that by including the nanopatterned point contact structure, the interface defect concentration lowers, which ultimately leads to an increase of solar cell electrical performance mostly by increase of the open circuit voltage. Gains to the short circuit current are distributed between an increased rear optical reflection and also due to electrical effects. Our approach of mixing several techniques allowed us to make a discussion considering the different passivation gains which has not been done in detail in previous works. A solar cell with a nanopatterned rear contact and a 350 nm thick CIGS absorber provided an average power conversion efficiency close to 10%.